Critical review of the role of ash content and composition in biomass pyrolysis - Puri, Lokeshwar; Hu, Yulin; Naterer, Greg (Frontiers in Fuels, 2024)
In the face of environmental challenges (e.g., dramatically increasing greenhouse gas emissions and climate change), it is utmost of importance to sustainable energy systems. Biomass consisting of agricultural and forest waste, municipal solid waste, and aquatics, has been identified as alternative and promising fuel sources. Thermochemical conversion approaches like pyrolysis can turn various types of biomass into three valuable product streams, namely, bio-oil, biochar, and syngas. To date, past review articles have considered the major operating parameters of kinetics, chemistry, and the application of pyrolysis products. However, ash content is one of the key biomass components that lacks investigation on its influence during biomass pyrolysis with respect to products yield and properties. This review article examines: i) the ash content and composition in different types of biomass; ii) effects of ash content on catalytic pathway and biomass thermal degradation; iii) ash related problems in the thermal degradation of biomass; and iv) available deashing techniques for biomass. The review aims to provide new understandings and insights regarding the effects of ash content and composition on biomass pyrolysis.